Readability in Classroom Practice of Report Text as Reading Material of Eleventh Graders - Yunita, Lifatur Rohmah; Suharsono, Suharsono; Munir, Ahmad (Journal of English Language and Literature (ISSN: 2368-2132), 2017)
This study is aimed to explain the readability of report text taken from “Bahasa Inggris Kelas 11” published by Kementrian Pendidikan dan Kebudayaan based on readability formula evaluated by expert, in classroom practice and to know whether the readability of report text in classroom practice correspond with the readability of report text evaluated by expert. This study was a qualitative research. The data gained from observation, interview and documentation. The research subject was the students of eleventh grader of SMA Al – Islam Krian. To analyse the data, the researcher used three stages that proposed by Ary et al. (2010:220), they are, 1) organizing and familiarizing, 2) coding and reducing and 3) interpreting and presenting. There are some findings were obtained for this study. The first finding of this study shows that the readability of report text evaluated by expert was in the difficult level for eleventh graders. Second finding shows students enjoyed the material as well. They could understand the material easily and find the six components of reading as has been stated by Marshall (1979) appropriately. For the last finding, it could be seen that no one of the students got under the minimum score from the Minimum learning Standard. In conclusion, readability of report text that had been conducted by expert was not in correspondence with readability of report text in the classroom practice. Since readability of the text did not only depend on the length of the letters, words and sentences only because the role of the readers was also important to be considered. It was supported by (Armbruster et al., 1985); Fulcher (1997). They stated that the formulas